Determination of zinc and iron in wheat using laser-induced breakdown spectroscopy. (9th November 2018) - Atta, Babar Manzoor; Saleem, Muhammad; Haq, S U; Ali, Hina; Ali, Zulfiqar; Qamar, Maqsood
Abstract: The potential of laser-induced breakdown spectroscopy (LIBS) has been used to determine the micronutrients (iron and zinc) in wheat, which is a staple food and the most widely cultivated crop in Pakistan. Wheat samples consisted of commercial and candidate varieties and a fortified wheat flour (FWF). The LIBS spectrum were recorded from wheat flour pellets using a Q-switched Nd:YAG laser focused on the surface of the wheat sample. Twenty-five single shot spectra were recorded at different sites of the same pellet. The data were normalized to exclude shot-to-shot laser energy variations and then the averaged emission spectrum was used for further analysis. According to the NIST atomic data base and the related literature, the most intense emission lines of zinc at 202.54, 206.20 and 213.85 nm and iron at 238.20, 259.93, 275.57, 344.06 & 373.48/373.71 nm have been detected in the LIBS spectra of wheat genotypes, which has been used to determine their relative intensities. Significant variation among the genotypes was identified for these minerals. In addition, principal component analysis (PCA) has been performed to statistically classify the wheat varieties based on their iron and zinc emission intensities. The PCA grouped the data into clusters based on the similarities in their micronutrient. The highest zinc was identified in NR-488, Zincol-2006 and NARC-2011. Likewise, the strongest iron intensities were observed in FWF, Borlaug-2016 and NR-486. These findings may assist breeders in the selection of genotypes with high micronutrients coupled with high grain yield, and other desirable traits essential for variety release. The present study has validated LIBS as a characterization tool for inferring micronutrients in the staple food.